Tomography of the red supergiant star μ Cep. Issue Volume 14:Issue S343(2019) (August 2018) - Kravchenko, K.; Chiavassa, A.; Van Eck, S.; Jorissen, A.; Merle, T.; Freytag, B.
Abstract: A tomographic method, aiming at probing velocity fields at depth in stellar atmospheres, is applied to the red supergiant star μ Cep and to snapshots of 3D radiative-hydrodynamics simulation in order to constrain atmospheric motions and relate them to photometric variability.